Development and implementation of a decision pathway for general practitioners for the management or referral of suspected allergy - Ray B. Jones; Emily J. Ashurst; Dafydd Jones; Roland Gude; Edward Kaminski (SAGE Publishing, 2014)
Many patients with suspected allergy are referred to specialist care inappropriately. We aimed to develop and implement an online decision pathway to aid General Practitioners' (GPs) management decisions in suspected allergy. Our study involved 1487 GPs, 3 referral management centres, 5 GP system suppliers, 4 primary care trusts, and 1 specialist allergy clinic. The pathway was implemented by 3/5 GP system suppliers, published to Map of Medicine and on a specialist clinic website. In the first year, the pathway ranked in the top 10/160 local care maps accessed via Map of Medicine and was viewed 900 times. Only 96 GPs registered to use the clinic website. Only 110 (7%) GPs responded to the feedback request, of which 13/110 (12%) had used the pathway; nearly all thought it useful. It was used by referral management centres as explanation of rejected referrals. Alternative approaches to embed its use are required.